Total Ankle Arthroplasty vs Ankle Arthrodesis: A Comparative Study of Patient Reported Outcomes. Issue 2 (10th April 2018) - Clanton, Thomas; Matheny, Lauren; Chang, Angela
Category: Ankle, Ankle Arthritis Introduction/Purpose: Ankle arthritis is a debilitating disorder which significantly limits activities of daily living and can lead to reduced quality of life. Total ankle arthroplasty(TAA) and ankle arthrodesis are common treatments for ankle arthritis; however, patient indications may differ based on individual patient needs. Few studies compare proportional hazard modeling, survivorship and patient-centered outcomes following these two procedures, which may be useful in determining the appropriate procedure for end-stage ankle arthritis in different patient populations. The purpose of this study was to determine proportional hazards for the risk of failure in patients who underwent TAA vs. arthrodesis, as well as survivorship and outcomes. Methods: All patients >18 years, between January 2009 and November 2013, who underwent TAA or ankle arthrodesis by a single surgeon for treatment of ankle arthritis were included. Patients completed a subjective questionnaire at minimum 2-years following index surgery. Outcomes measures included Foot and Ankle Ability Measure(FAAM), Foot and Ankle Disability Index(FADI), Lysholm, WOMAC, SF-12 physical component summary(PCS) and mental component summary(MCS), Tegner activity scale and patient satisfaction with outcome. Detailed surgical data/intraoperative findings were documented at time of surgery. All data were collected prospectively. Cox proportional hazard modeling and survivorship analysis were performed to assess differences between the two cohorts. Survivorship utilizing Kaplan-Meier method, using a log-rank test, was used to compare median survivorship. Cox-proportional hazard model was conducted to compare hazard rates of surgical failure for patients in each cohort, while adjusting for age at surgery, body mass index(BMI) and sex. All outcome measures were compared between cohorts. Results: There were 97 patients available for analysis. Eight patients failed surgery(9.2%). Demographic data were documented (Table 1). There was no significant difference in failures (TAA=2 failures (6.5%) vs. arthrodesis=6 failures (11.8%)(p=0.709). There was no significant difference in survivorship of surgery between the arthrodesis cohort and the TAA cohort(p=0.785)(Table 1, Figure 1). There was a decrease in survivorship at 4 years in TAA cohort compared to arthrodesis cohort, which was not significant. The hazard ratio was 0.804 [95%CI: 0.111–5.842], indicating that cohort did not have a significant effect on the hazard of surgical failure(p=0.829). Sex, age and BMI did not have a significant effect on the hazard of surgical failure(p>0.05). There was no significant difference in any outcome measures between cohorts(Table 1). Conclusion: There was no significant difference in survivorship or in the hazard of surgical failure based on cohort (TAA and arthrodesis) while accounting for sex, age at surgery and BMI. There was no significant difference in the hazard of surgical failure for factors including age at surgery, BMI or sex. There was no significant difference in survivorship or outcomes between cohorts. Total ankle arthroplasty seems to provide similar results as arthrodesis; however, there was a decrease in survivorship at 4 years in the TAA cohort. Although not significant, this may indicate that survivorship differs during the longer-term follow-up period.